Prevalence of β-lactamases and carbapenemases in cultures of kidney recipients treated at a university hospital in Ceará - Antonia C. LIMA; Andreza A. ANDRADE; Thaynara C. FREITAS; Fernando C. PEDROZA; Ana B. RODRIGUES; Glaydiane A. SOUSA; Lizandra M. OLIVEIRA; Denis F. CASTRO; Henry C. REIS; Alene B. OLIVEIRA; Alexsandra N. PINHEIRO (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2022)
Objective: The present study aimed to identify the prevalence of β-lactamases and carbapenemases in cultures of kidney recipients treated at a university hospital in Fortaleza, Ceará. Methods: This is a descriptive and retrospective study, carried out between January 2017 and December 2020 at a university hospital in Fortaleza, Ceará. Patients were included in the study, admitted to the renal transplant ward (12 beds), monitored by pharmacists from the "Antimicrobial Stewardship Program" (ASP) and using antimicrobials standardized in the institution as a therapeutic reserve for at least minimum 48 hours. Results: Male patients prevailed (53.2%), clinical outcome of discharge and death in the total of both sexes was 96.5% and 3.5% respectively. A total of 684 cultures were analyzed, but only 166 had growth of microorganisms, being 9 of fungal nature, 34 gram-positive bacteria and 123 gram-negative bacteria. Among the isolates, the highest prevalence was of Klebsiella pneumoniae 39.0% (n=47), with 54.3% (n=19) bacteria producing extended spectrum beta-lactamases (ESBL) and 88.2% (n= 15) carbapenem-resistant enterobacteriaceae (ERC) and regarding the types of culture, a greater number of urine cultures were observed (57.7%). Conclusions: A high prevalence of Klebsiella pneumoniae was observed, and it was also the most frequent microorganism in ESBL and ERC. Infections after kidney transplantation are causes of significant morbidity and mortality, and often difficult to diagnose in immunosuppressed patients, it is interesting that the rational use of antimicrobials is well established, considering that the more exposure to the use of these drugs, the favoring of the selection of multidrug-resistant strains.